Analysis of Microplastic Content in Sediments of the Pasir Sakti Mangrove Ecosystem, East Lampung - Suhanda, Delilla; Syari, Chalida; Dwiputra, Mohammad Ashari; Rajab, Muhammad Arhan; Kurniawan, Alvin (Jurnal Laut Khatulistiwa, 2026)
Mangroves as buffer ecosystems possess a natural capacity to trap pollutants originating from both terrestrial and marine sources, including microplastics. This study aimed to identify and map the characteristics and distribution of microplastics in the sediments of the Pasir Sakti mangrove ecosystem. The study employed a descriptive–quantitative approach combining laboratory and geospatial analyses. Sediment samples were collected from five stations using purposive sampling and analyzed through granulometric analysis, microplastic extraction using a NaCl solution, and morphological identification of microplastics using a microscope. Ecological parameters, including water quality and mangrove vegetation structure, were measured in situ. The distribution of microplastics was visualized as thematic maps using a Geographic Information System (GIS). The results of water quality analysis showed temperatures ranging from 29.7 to 31.9 °C, salinity of 9–11 ppt, relatively high water pH values of 8.76–10.8, acidic soil pH values of 3–6.7, low water transparency of 22–30 cm, and very high TDS concentrations of 6,825–7,967 ppm. The sediment at the study site was predominantly classified as sand. The mangrove vegetation was dominated by Avicennia sp., with a density ranging from 0.24 to 0.67 individuals/m². A total of 259 microplastic particles were identified, comprising film, fragment, foam, fiber, and pellet types. Film was the dominant microplastic type, with a total of 160 particles.